The impact of credit risk on the business performance of commercial banks in Vietnam - Vo, Thanh Tùng; Le, Văn Hải (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2025)
This study examines the impact of credit risk on the business performance of commercial banks in Vietnam from 2013 to 2023. Commercial banks play a crucial role in the modern economy, not only as financial intermediaries but also as key providers of credit to the economy. Credit activities constitute a significant portion of banks' income, making credit risk management essential for evaluating their business performance. This research employs quantitative regression models, including the Pool (OLS), Fixed Effects Model (FEM), Random Effects Model (REM), and Feasible Generalized Least Squares (FGLS), to analyze data from 27 commercial banks operating in Vietnam. The findings indicate that credit risk significantly impacts the banks' business performance, especially in terms of managing bad debts and credit provisions. Based on these results, the study proposes solutions to mitigate credit risk and improve business performance, contributing to the stability and sustainable development of the banking system in Vietnam.